Impresora modular 3D multifunción para el laboratorio de electromecánica de la Universidad Técnica de Cotopaxi Extensión La Maná". - Diaz Rojas, Estiben Bladimir (2023)
The current research work is based on implementing a "Multifunction Modular 3D Printer for the laboratory at the Technical University of Cotopaxi - La Maná extension". The 3D printer which uses laser engraving is determined for the practices of the students of the electromechanics career in the laboratory of manufacturing technologies. The 3D printer is a machine that is capable of making replicas on three-dimensional design. Its main value is that it takes a stored design in a computer file and turns it into reality, it means into a volumetric piece with length, width, and height with the use of a free licensed program CAD. The 3D printer is controlled by a controller which is the main part of its system to control the stepper motors and to achieve movements in three axes, so achieving the desired shape of the 3D printer and laser engraving. The machine uses a filament PLA-TPU-PVA-ABS, the power consumption and recorded material are low cost. Depending on the size of the figure, the price varies from $86 the maximum size, from 200 mm3 allowed by the printer with good surface finishes. In the laser engraving, the size of 200 mm2 at its maximum capacity with supported material: wood engraving, triplex, leather, acrylic, pressed cardboard, and plastic; each material has its own value and price to make the laser engraving: wood: $24, triplex: $26, leather: $26, acrylic: $29, pressed cardboard: $22, and plastic: $26.With the use of this printer, the students of the electromechanics career at the Technical University of Cotopaxi - La Maná extension will be able to access to this technology easily and at low cost and to acquire additional skills.